UPAYA BAKOR PAKEM DALAM MENCEGAH PERKEMBANGAN POTENSI RADIKALISME DI KABUPATEN KEPAHIANG - Muhammad Ridwan (Sekolah Pasca Sarjana IAIN Bengkulu, 2016)
Abstract: Background This study is a radical ideology as a basis for the alleged terror bombing. Indonesia makes this ideology as it feared more widespread. Kepahiang District participated prevent this ideology does not escalate. Formulation of the problem in this research is: How Bakor Pakem efforts in preventing the development potential of radicalism in the District Kepahiang?. This study examined the potential radicalism in Kepahiang and preventive measures by Bakor Pakem. This type of study is a qualitative research with descriptive and analytical nature. The study found that there is a potential Kepahiang District of religious radicalism. Some residents Kepahiang is a member of the organization Hizb ut-Tahrir Indonesia (HTI), the Islamic Defenders Front (FPI) and the former followers of the Movement Fajar Nusantara (Gafatar). While in Kepahiang yet these organizations.Preventive measures that do Bakor Pakem are: first, to collect information that will be members of Bakor Pakem ranging from intelligence work by the police (Police) and the Indonesian Military (Kodim and Koramil). Second, the monthly reports submitted by the Office of National and Political Unity government Kepahiang District. The third discussion meeting held as chairman of the State Attorney Bakor Bakor Pakem Pakem with members. Fourth. Prevention is done by each agency and organization Bakor Pakem corresponding basic tasks and functions of each. The Police with intelligence work and guidance of the community, the military intelligence and guidance of an integrated, the Ministry of Religious Affairs with public education, the Indonesian Ulema Council with public education, the Forum for Religious Harmony (FKUB) with coordination and communication between religious communities and socialize together involve berbegai elements of society, And the declaration of refusal schools of ISIS and radicalism involving various organizations and educational institutions.